Analysis Of The Impact Of Intership Activities In Improving Skill and Expertise Of Accounting Study Program Students - Aliah, Nur; Fachruddin, Wan (Accounting and Business Journal, 2023)
This study aims to determine the impact of internship activities in improving student skills andexpertise in accounting study programs. In this research study using a descriptive qualitativeapproach, where the data collection technique uses direct interviews and surveyer analysis to theobject of research, namely accounting students who have carried out internships in governmentoffices in the city of Medan. Based on the results of survey analysis to 8 students who conductedthe MBKM program implemented by Panca Budi University, the internship program will provideadditional competencies, 50% of students feel that there is an increase in soft skills after MBKMin developing competencies / skills as a provision for work after graduation. MBKM is importantto do in preparation for the post-campus period. 62.5% of students feel that MBKM is inaccordance with the needs of future graduates. The MBKM program is expected to be a forumfor students to develop competencies both in soft skills and hard skills development.